Given, 1) \(\displaystyle{y}={0.8}^{x}\)

2) \(\displaystyle{y}=-{3}{x}-{8}\)

3) \(\displaystyle g{{\left({x}\right)}}={\left(\frac{1}{{2}}\right)}^{x}\)

we have to find decay factor

Here 1) \(\displaystyle{y}={0.8}^{x}\) which is exponential function of the form of

\(\displaystyle{y}={a}{\left({b}\right)}^{x}\text{where}\ {a}={1},{b}={0.8}\)

Hence, the decay factor is: 0.8

2) \(\displaystyle{y}=-{3}{x}-{8},\) Decay factor is N

3) \(\displaystyle g{{\left({x}\right)}}={\left(\frac{1}{{2}}\right)}{x},\)

Decay factor is \(\displaystyle\frac{1}{{2}}\)

2) \(\displaystyle{y}=-{3}{x}-{8}\)

3) \(\displaystyle g{{\left({x}\right)}}={\left(\frac{1}{{2}}\right)}^{x}\)

we have to find decay factor

Here 1) \(\displaystyle{y}={0.8}^{x}\) which is exponential function of the form of

\(\displaystyle{y}={a}{\left({b}\right)}^{x}\text{where}\ {a}={1},{b}={0.8}\)

Hence, the decay factor is: 0.8

2) \(\displaystyle{y}=-{3}{x}-{8},\) Decay factor is N

3) \(\displaystyle g{{\left({x}\right)}}={\left(\frac{1}{{2}}\right)}{x},\)

Decay factor is \(\displaystyle\frac{1}{{2}}\)